Predicting two types of recidivism among newly released prisoners: first addresses as “Launch Pads” for pecidivism or reentry success - Clark, Valerie A. (Crime & delinquency, 2016)
Separate studies have shown that a variety of postrelease housing placements for returning prisoners can significantly influence recidivism. Research has also found that contextual factors such as economic disadvantage can also significantly predict recidivism. This study combines those lines of research by examining the effects of five categories of postrelease housing placements as well as contextual measures of economic disadvantage on recidivism for newly released Minnesota state prisoners. Using multilevel analysis techniques, this research found that with one exception, certain postrelease housing situations, along with several other individual-level control variables, were more robust predictors of recidivism than contextual measures of disadvantage and poverty. This study highlights the significant impact that postrelease housing placements can have on the reentry process.